2011
DOI: 10.1109/tsp.2010.2104148
|View full text |Cite
|
Sign up to set email alerts
|

Complexity and Performance Comparison of Filter Bank Multicarrier and OFDM in Uplink of Multicarrier Multiple Access Networks

Abstract: Abstract-We compare filter bank multicarrier (FBMC) and orthogonal frequency-division multiplexing (OFDM) in the uplink of a multiple access network. Our study reveals that the high sensitivity of OFDM to carrier frequency offset (CFO) among different users and the need for interference cancellation methods to reduce this sensitivity leads to very complex and yet not very high performance systems. In FBMC-based networks, on the other hand, near-perfect performance is achieved without any need for interference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
50
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(52 citation statements)
references
References 21 publications
(37 reference statements)
2
50
0
Order By: Relevance
“…It was concluded that the performance degradation from synchronization errors is negligible provided that at least one subcarrier is left void between adjacent multiuser transmissions. The same conclusion has been drawn in [59]. In OFDMA, a single subcarrier does not suffice to separate the signals from different users.…”
Section: F Robustness Against Synchronization Errorssupporting
confidence: 71%
See 1 more Smart Citation
“…It was concluded that the performance degradation from synchronization errors is negligible provided that at least one subcarrier is left void between adjacent multiuser transmissions. The same conclusion has been drawn in [59]. In OFDMA, a single subcarrier does not suffice to separate the signals from different users.…”
Section: F Robustness Against Synchronization Errorssupporting
confidence: 71%
“…In OFDMA, a single subcarrier does not suffice to separate the signals from different users. At the price of a complexity increase, the sensitivity to synchronization errors can be reduced by resorting to interference mitigation techniques [59], [60]. Section IV-C4 further delves into the robustness against synchronization errors, by carrying out a performance evaluation of FBMC/OQAM and OFDM when tight synchronization is not attained.…”
Section: F Robustness Against Synchronization Errorsmentioning
confidence: 99%
“…Multicarrier schemes based on filter banks (FBMC) have recently shown the potential of overcoming such drawbacks [8,9], thus providing an attractive alternative to OFDM, at the cost of some additional complexity http://asp.eurasipjournals.com/content/2014/1/66 and delay [10]. When combined with offset quadrature amplitude modulation (OQAM), prototype filters with good localization in both time and frequency are possible, resulting in the so-called FBMC/OQAM modulation scheme [11].…”
Section: Introductionmentioning
confidence: 99%
“…In filter bank multicarrier (FBMC) systems such as IOTA, on the other hand, near-optimal performance is achieved without any additional signal processing, such as interference cancellation, due to the excellent frequency-localized filters employed in FBMCbased systems [12]. The added complexity arising from IC blocks in an OFDM-based system makes it significantly more complex than its IOTA counterpart.…”
Section: Introductionmentioning
confidence: 99%